A three-dimensional culture system for generating cardiac spheroids composed of cardiomyocytes, endothelial cells, smooth-muscle cells, and cardiac fibroblasts derived from human induced-pluripotent stem cells - Kahn-Krell, Asher; Pretorius, Danielle; Guragain, Bijay; Lou, Xi; Wei, Yuhua; Zhang, Jianhua; Qiao, Aijun; Nakada, Yuji; Kamp, Timothy J.; Ye, Lei; Zhang, Jianyi (Frontiers in Bioengineering and Biotechnology, 2022)
Cardiomyocytes (CMs), endothelial cells (ECs), smooth muscle cells (SMCs), and cardiac fibroblasts (CFs) differentiated from human induced-pluripotent stem cells (hiPSCs) are the fundamental components of cell-based regenerative myocardial therapy and can be used as in-vitro models for mechanistic studies and drug testing. However, newly differentiated hiPSC-CMs tend to more closely resemble fetal CMs than the mature CMs of adult hearts, and current techniques for improving CM maturation can be both complex and labor-intensive. Thus, the production of CMs for commercial and industrial applications will require more elementary methods for promoting CM maturity. CMs tend to develop a more mature phenotype when cultured as spheroids in a three-dimensional (3D) environment, rather than as two-dimensional monolayers, and the activity of ECs, SMCs, and CFs promote both CM maturation and electrical activity. Here, we introduce a simple and reproducible 3D-culture–based process for generating spheroids containing all four cardiac-cell types (i.e., cardiac spheroids) that is compatible with a wide range of applications and research equipment. Subsequent experiments demonstrated that the inclusion of vascular cells and CFs was associated with an increase in spheroid size, a decline in apoptosis, an improvement in sarcomere maturation and a change in CM bioenergetics.